(3GdESJQGJjLjI hGdJNWjW GdESJQGJjLjs - (3HdGd Nda(B, (3GdScGQfIs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2015)
(3eGgjI GdJNWjW GdGSJQGJjLj , YedjI GdJNWjW GdGSJQGJjLj , JMOjO hJYQja GdGJLGg GdGSJQGJjLj, GdJMdjd hGdJTNjU GdHjFj, UjGZI hEYOGO GdNWI, UjGZI GdCgOGa GdESJQGJjLjI , GdHOGFd hGdNjGQGJ GdESJQGJjLjI, JfajP GdNWI GdESJQGJjLjI, GdQbGHI hGdeJGHYI hGdJbjje ddNWI GdESJQGJjLjI, MGdGJ OQGSjI aj GdJNWjW GdESJQGJjLj(B.s
Keywords: (3EOGQI GdCYeGds; (3GdJNWjWs; (3Jbjje GdCOGAs